Khayelitsha 2001 - 2011: 10 years of primary care HIV and TB programmes - Daniela Belen Garone; Katherine Hilderbrand; Andrew M Boulle; David Coetzee; Eric Goemaere; Gilles Van Cutsem; Donela Besada (AOSIS, 2011)
Tuberculosis (TB) and HIV care in Khayelitsha, and in South Africa as a whole, has overcome numerous obstacles in the past three decades. This article highlights what has been achieved in Khayelitsha, describes the key clinical programme and policy changes that have supported universal coverage for HIV and TB care over the last 10 years, and outlines the challenges for the next decade.